Preparation of gasified ash-based zeolite molecular sieve PEI modification and CO2 adsorption performance - Duo ZHANG; Chengcheng JIAO; Hu WEN; Jun DENG; Xiaowei ZHAI; Chun LIU; Yang DU (Meitan xuebao, 2025)
Aiming at the problems of bulk solid waste accumulation and environmental pollution caused by the large output and low utilization rate of coal-to-oil gasification ash, and combining with the strategic goal of "double-carbon", the idea of combining gasification ash functional filling, CO2 absorption and storage, and the reuse of air mining area is proposed. Using coal-to-oil gasification slag as the base material, the gasification slag was first pretreated by high-temperature calcination and acid leaching, and then alkali fusion-hydrothermal synthesis was used to prepare gasification slag-based zeolite molecular sieves, and finally, the gasification slag-based zeolite molecular sieves were optimized by using the organic amine polyethyleneimine (PEI). The zeolite molecular sieves before and after modification were characterized by XRD, SEM, BET, FTIR and other experiments, and the adsorption law of CO2 gas by zeolite molecular sieves before and after modification was investigated to analyze the effects of loading and temperature on the adsorption performance. The results show that the PDF#39-0222 standard maps, regular cubic crystal particles, [SiO4]4− and [AlO4]5− tetrahedral structures indicate that zeolite molecular sieves have been successfully prepared by using the coal-to-oil gasification ash solid waste, and the N—H bonds in RNH2 and the C—H bonds in —CH3 indicate that PEI has achieved the optimized modification of the molecular sieves, and the adsorption patterns and adsorption properties of the zeolite molecular sieves for CO2 gas before and after the modification are clarified. CO2 adsorption mode and adsorption law before and after modification. Compared with the gasified ash raw material, the specific surface area of zeolite molecular sieve increased 30.24 times, the pore volume increased 21.04 times, the average pore diameter decreased 0.49 times, and the adsorption structure was significantly increased; the adsorption amount of CO2 by zeolite molecular sieve decreased with the increase of temperature, which indicated that the process of adsorption of CO2 was an exothermic physical adsorption. With the increase of PEI loading, the specific surface area, external surface area and pore volume gradually decreased, the average pore diameter gradually increased, and the amine group continued to attach easily to the agglomeration phenomenon, resulting in the weakening of physical adsorption capacity; the chemical reaction between amine group and CO2, which improved the chemical adsorption capacity of the molecular sieve. Under the condition of 298.15 K, the adsorption capacity of molecular sieve for CO2 decreased gradually with the increase of PEI loading, and the adsorption capacity of CO2 adsorption by A1-PEI-15% on CO2 was 92.71 cm3/g, which was increased by 36.74% compared with that before modification, and the adsorption capacity of the molecular sieve on CO2 increased with the increase of temperature at 15% PEI loading; the maximum adsorption capacity of the molecular sieve at 328.15 K was 111.06 cm3/g, which was increased by 19.79% compared with that at 298.15 K.